National transfer accounts and generational flows - Michael MacLennan; Bernardo L. Queiroz (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
The economic life cycle is characterised by three distinct phases: two phases of economic dependence and one phase of economic independence. In most societies, children consume resources generated by adults, transferred to them by family or by the public sector. The elderly, in turn, possess an accumulation of assets accrued during their active economic phase, and of resources produced and transferred by adults or other credit operations. Over each period of time, every society determines - by social norms, laws and individual decisions - the combination of mechanisms for resource allocation over life cycles. Intergenerational transfers represent a significant portion of the distributed production and time allocation over the life cycle and become increasingly important given the rapid demographic changes that have been happening around the world over the last decades. [...]
Keywords: 330; National Transfer Accounts; Generational Flows